Genetic risk mechanisms of posttraumatic stress disorder in the human brain. Issue 1 (24th October 2016) - Bharadwaj, Rahul A.; Jaffe, Andrew E.; Chen, Qiang; Deep‐Soboslay, Amy; Goldman, Aaron L.; Mighdoll, Michelle I.; Cotoia, John A.; Brandtjen, Anna C.; Shin, JooHeon; Hyde, Thomas M.; Mattay, Venkata S.; Weinberger, Daniel R.; et al.
Abstract : Posttraumatic stress disorder (PTSD) follows exposure to a traumatic event in susceptible individuals. Recently, genome‐wide association studies have identified a number of genetic sequence variants that are associated with the risk of developing PTSD. To follow up on identifying the molecular mechanisms of these risk variants, we performed genotype to RNA sequencing–derived quantitative expression (whole gene, exon, and exon junction levels) analysis in the dorsolateral prefrontal cortex (DLPFC) of normal postmortem human brains. We further investigated genotype–gene expression associations within the amygdala in a smaller independent RNA sequencing (Genotype‐Tissue Expression [GTEx]) dataset. Our DLPFC analyses identified significant expression quantitative trait loci (eQTL) associations for a "candidate" PTSD risk SNP rs363276 and the expression of two genes: SLC18A2 and PDZD8, where the PTSD risk/minor allele T was associated with significantly lower levels of gene expression for both genes, in the DLPFC. These eQTL associations were independently confirmed in the amygdala from the GTEx database. Rs363276 "T" carriers also showed significantly increased activity in the amygdala during an emotional face‐matching task in healthy volunteers. Taken together, our preliminary findings in normal human brains represent a tractable approach to identify mechanisms by which genetic variants potentially increase an individual's risk for developing PTSD. © 2016 Wiley Periodicals, Inc. Abstract : PTSD genetic risk mechanisms in the human brain. Legend: The graphical overview of our research findings is a proven example of how genetic risk mechanisms potentially operate through multiple modalities including gene expression (RNA sequencing), epigenetics (DNA methylation), and neurophysiology (fMRI) in the human brain. Using "risk" DNA biomarkers such as SNPs improves the tractability insofar as studies addressing plain case–control differences are confounded by substance abuse, treatment, and epiphenomena that are unknown in the absence of a tractable genetic sequence biomarker. To illustrate, we show associations for allelic variation at candidate PTSD "risk" SNP rs363276 (CC/CT/TT) where the risk allele "T" carriers show significant changes across multiple modalities. We present an approach of how we can map mechanisms associated with clinical risk that progress towards either "resilience to" or "risk of" developing PTSD in "normal" controls. Now that we have dissected these mechanisms in "normal" brains, the next step would include evaluating these findings in the brains of subjects diagnosed with PTSD where any differences in these associations can be attributable to PTSD disease phenomena, especially when a control psychiatric group such as "major depression" or "bipolar disorder" is included.